Intelligent robotic navigation as a child companion - Chew, Zhi Kang (Nanyang Technological University, 2022)
The advent of technology in robotics and artificial intelligence has invoked the interests of many into thinking how it can complement and improve our everyday lives. With the recent rise in number of tragic incidents that occurred when children were left unsupervised at home, robotics may provide us with a solution by tracking and monitoring the child autonomously and informing the parent immediately when the child falls and gets hurt. There are 3 phases involved in this project. In phase 1, we will mainly explore and test the functionalities of the TurtleBot3, including Teleoperation, SLAM (Simultaneous Localization and Mapping), Navigation and the Raspberry Pi Camera capabilities. In phase 2, we will make use of the real time camera feed from the Raspberry Pi Camera to perform Object Recognition using Computer Vision and TensorFlow. In phase 3, the Object Recognition capabilities of the TurtleBot3 will be used to identify and follow a child’s movement and to inform the parent when the child had fell.